Temperature mediated ‘photonic hook’ nanoparticle manipulator with pulsed illumination; Nanoscale Advances; Vol. 2, iss. 6 - Spector M. Marat; Ang A. S. Angeleene; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich; Karabchevsky A. (2020, 2020)
Title screen